On the causal association between exposure to leather dust and nasal cancer: further evidence from a case-control study. Issue 2 (February 1986) - Merler, E; Baldasseroni, A; Laria, R; Faravelli, P; Agostini, R; Pisa, R; Berrino, F
Abstract : A case-control study was performed on the incident cases of nasal cavity tumours which occurred between 1968 and 1982 among the residents of Vigevano (Lombardy region, northern Italy). This area is characterised by a high prevalence of shoemakers (especially in leather); the activity has predominated in Vigevano since the beginning of this century. Twenty one cases were identified (16 men and five women); 20 were histologically confirmed as nasal epithelial tumours; 17 had already died at the time of interview and the occupational history was obtained from the next of kin. Two controls per case were selected from the general population and matched by vital status, age, sex, and residence. The overall odds ratio for the subjects exposed to leather dust was 47.1 for men and 3.5 for women. The odds ratio was higher for adenocarcinoma and among the workers exposed to the worst working conditions. A significant trend for the level of exposure to leather dust was found. Nevertheless, even the jobs characterised by a relatively low exposure were found to have a significantly higher risk (OR = 7.5). Smoking habits and exposure to solvents are unlikely to confound the relation between exposure to leather and nasal tumours.